2000
DOI: 10.1177/002215540004800105
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Mitochondrial 60-kD Heat Shock Chaperonin Protein (Hsp60) in Pituitary Growth Hormone Secretory Granules and Pancreatic Zymogen Granules

Abstract: SUMMARYWe used quantitative immunogold electron microscopy and biochemical analysis to evaluate the subcellular distribution of Hsp60 in rat tissues. Western blot analysis, employing both monoclonal and polyclonal antibodies raised against mammalian Hsp60, shows that only a single 60-kD protein is reactive with the antibodies in brain, heart, kidney, liver, pancreas, pituitary, spleen, skeletal muscle, and adrenal gland. Immunogold labeling of tissues embedded in the acrylic resin LR Gold shows strong labeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 51 publications
(70 reference statements)
4
39
0
1
Order By: Relevance
“…The over-expression of hsp chaperones can depend on Cd-promoted denaturation and oxidation of proteins, and is probably linked to the increase of oxidative stress. Although hsp60 is mostly localized in the mitochondrial matrix, it has also been found in other subcellular localizations including the ER, cell surface, and unidentified vesicles and cytoplasmic granules [57] and also found to be over-expressed and localized in the cytoplasm of cancer cells [58]. In the current study, we report the presence of hsp60 in the cytoplasm of MDA-MB231 tumor cells and demonstrate that CdCl 2 exposure modifies the cytosolic level of the protein.…”
Section: Mitochondrial Gene Expressionsupporting
confidence: 53%
“…The over-expression of hsp chaperones can depend on Cd-promoted denaturation and oxidation of proteins, and is probably linked to the increase of oxidative stress. Although hsp60 is mostly localized in the mitochondrial matrix, it has also been found in other subcellular localizations including the ER, cell surface, and unidentified vesicles and cytoplasmic granules [57] and also found to be over-expressed and localized in the cytoplasm of cancer cells [58]. In the current study, we report the presence of hsp60 in the cytoplasm of MDA-MB231 tumor cells and demonstrate that CdCl 2 exposure modifies the cytosolic level of the protein.…”
Section: Mitochondrial Gene Expressionsupporting
confidence: 53%
“…We and others have shown that overexpression and phosphorylation of HSP27 and induction of HSP70 in pancreatic acinar cells protect against cerulein-induced pancreatitis (2,12). It has been found that cellular organelles like mitochondria in acinar cells express HSP60 (5,13). Along the synthesis and secretory pathway of pancreatic enzymes in acinar cells, there is an intimate coincidence of HSP60 with pancreatic lipase, amylase, and trypsin confirmed by immunoprecipitation assays; i.e., when HSP60 antibody is added to the isolated zymogen granule extracts, coprecipitation of HSP60 with digestive enzymes occurs (13,18).…”
Section: Discussionmentioning
confidence: 94%
“…It not only exists in the mitochondria of pancreatic acinar cells, but also presents in the rough endoplasmic reticulum (RER), in Golgi body (G), in zymogen granules (ZG), and in the secretory pathway of pancreatic enzymes in acinar cells (Li et al 2003;Cechetto et al 2000). It is thought that Cpn60 residing in the mitochondria plays a different role from that of the protein located in the RER-G-ZG Keskin et al 2002).…”
Section: Introductionmentioning
confidence: 99%